2008
DOI: 10.1097/iae.0b013e31815e9313
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis After 25-Gauge and 20-Gauge Pars Plana Vitrectomy

Abstract: Clinician grading of retinopathy severity had moderate agreement with RC grading and might be useful for placing eyes into broad baseline categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
199
7
9

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(226 citation statements)
references
References 8 publications
11
199
7
9
Order By: Relevance
“…The incidence of endophthalmitis (1.6%) was eight times higher than what Kunimoto and Kaiser 18 and the current study reported in 25-gauge vitrectomy and two times larger than what Scott reported. 15 However, Shaikh's study population was small and not powered to detect a true difference in endophthalmitis rates following the two surgical techniques.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of endophthalmitis (1.6%) was eight times higher than what Kunimoto and Kaiser 18 and the current study reported in 25-gauge vitrectomy and two times larger than what Scott reported. 15 However, Shaikh's study population was small and not powered to detect a true difference in endophthalmitis rates following the two surgical techniques.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Scott et al 15 recently retrospectively examined 6375 patients who underwent 20-gauge PPV and 1307 patients who underwent 25-gauge PPV. The incidence of endophthalmitis was 0.03% for 20-gauge PPV compared to 0.84% for 25-gauge PPV (Po0.0001), which represents a 24 times increased risk with the sutureless 25-gauge system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 Similar results were reported from the Bascom Palmer Eye Institute with a rate in 25-gauge patients of (0.84% 11/1307 eyes) compared with 20-gauge vitrectomy (0.03%; 2/6375). 35 Since these 36 The surgeons in this latter study emphasised the importance of conjunctival irrigation, ensuring sclerotomy closure and removal of peripheral vitreous as important preventative measures. Another potential problem is hypotony that is directly related to leaking wounds.…”
Section: Small Gauge Surgerymentioning
confidence: 99%